Some Fejer Type Inequalities for Harmonically-Convex Functions with Applications to Special Means - M. A. Latif; S. S. Dragomir; E. Momoniat (International Journal of Analysis and Applications, 2017)
In this paper, the notion of harmonic symmetricity of functions is introduced. A new identity involving harmonically symmetric functions is established and some new Fejer type integral inequalities are presented for the class of harmonically convex functions. The results presented in this paper are better than those established in recent literature concerning harmonically convex functions. Applications of our results to special means of positive real numbers are given as well.